Allocating species in Grime’s strategy space: an alternative to trait-based approaches - Fernando Pedraza; Carlos Martorell (Botan‪ical Sciences, 2019)
Background:  The three primary-strategy theory proposed by Grime identifies stress and disturbance as key environmental factors leading to the emergence of distinct plant strategies. These are defined by a combination of stress and disturbance tolerance. Plant strategies are usually inferred from sets of traits, but this may lead to circular reasoning and artificial restrictions to species’ distribution in strategy space.